Kebijakan Pajak Indonesia Menanggapi Krisis COVID-19: Manfaat bagi Wajib Pajak - Padyanoor, Aswin (E-Jurnal Akuntansi; Vol 30 No 9 (2020), 2020)
The economy has changed dramatically since the COVID-19 outbreak began. The impact that occurred in Indonesia was almost on all fronts, and the Government continued to issue policies due to this impact. Tax policies that are designed to provide incentives for affected taxpayers are expected to increase economic growth. This research was conducted to map 14 Tax Policies in three Regulations issued by the Government based on the objective of reducing the economic impact of the COVID-19 pandemic. The study used a qualitative method with a descriptive approach obtained. Then perform data analysis using three stages of analysis techniques in the form of data collection, data reduction, and concluding. The results of the study state that Indonesia has issued a policy to help taxpayers who are affected by COVID-19. Benefits for taxpayers, namely a reduction in rates to an exemption from income tax, the goal is that the economy which has stopped moving up becomes stable. Keywords: Tax Incentives; Tax Policy; Taxpayers.